2006
DOI: 10.1093/aje/kwj089
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes, Infant Mortality, and Arsenic in Drinking Water in West Bengal, India

Abstract: Between 2001 and 2003, the authors studied pregnancy outcomes and infant mortality among 202 married women in West Bengal, India. Reproductive histories were ascertained using structured interviews. Arsenic exposure during each pregnancy, including all water sources used, was assessed; this involved measurements from 409 wells. Odds ratios for spontaneous abortion, stillbirth, neonatal mortality, and infant mortality were estimated with logistic regression based on the method of generalized estimating equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 32 publications
1
103
1
Order By: Relevance
“…Our study suggests that such exposure produces adverse effects on pregnancy outcome, as the incidences of stillbirths and miscarriages significantly differ between the exposed and the control groups. A recent similar study done in West Bengal has suggested that high As exposure through groundwater increases the risk of stillbirth, but not of miscarriage (8). On the other hand, a study in Bangladesh (9) has reported higher incidence of stillbirths and miscarriages in pregnant women exposed to As through groundwater than in normal controls.…”
Section: Discussionmentioning
confidence: 96%
“…Our study suggests that such exposure produces adverse effects on pregnancy outcome, as the incidences of stillbirths and miscarriages significantly differ between the exposed and the control groups. A recent similar study done in West Bengal has suggested that high As exposure through groundwater increases the risk of stillbirth, but not of miscarriage (8). On the other hand, a study in Bangladesh (9) has reported higher incidence of stillbirths and miscarriages in pregnant women exposed to As through groundwater than in normal controls.…”
Section: Discussionmentioning
confidence: 96%
“…Arsenic and its methylated metabolites are accumulated in placenta and fetal tissues and subsequently exert toxic effects. This may result in fetal loss (Von-Ehrenstein 2006).…”
Section: Status Of Previous Pregnancy Complicationsmentioning
confidence: 99%
“…The latter have often been obtained through interviews carried out many years after a particular pregnancy, when a mother known to be exposed may, report more adverse effects than one with no known exposure. Increased risk of spontaneous abortion, stillbirth, preterm birth and neonatal death at elevated water arsenic concentrations were indicated in three, fairly small, studies two in Bangladesh and one in West Bengal, in which 192, 533, and 202 women of childbearing age, respectively, were interviewed about previous pregnancies (Ahmad et al, 2001;Milton et al, 2005;von Ehrenstein et al, 2006). In northern Chile, register-derived data on foetal and neonatal mortality in the town of Antofagasta was found to be elevated during a period (1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970) with increased arsenic concentration in drinking water (800 ”g/L) compared to that in the town of Valparaiso with essentially no arsenic in the drinking water (Hopenhayn-Rich et al, 2000).…”
Section: Effects Of Arsenic On Foetal Developmentmentioning
confidence: 99%